2022
DOI: 10.3390/plants11162094
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antioxidant and Antibacterial Properties of Extracts of Viscum continuum E. Mey. Ex Sprague, a South African Mistletoe

Abstract: Viscum continuum E. Mey. Ex Sprague is a woody evergreen semi-parasitic shrub that grows on the branches of other trees. It is used by African traditional healers for post-stroke management. This study reports on the qualitative phytochemical screening and the antioxidant and antimicrobial activities of Viscum continuum’s acetone, methanol, hexane and dichloromethane extracts. Standard protocols for the phytochemical screening of extracts were employed. TLC bio-autography was used for qualitative antioxidants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…This comes as a surprise as the literature information from Loranthus micranthus Linn. studies reported the presence of alkaloids in the DCM and MeOH extracts [ 13 ]. Perhaps their presence in the samples we analyzed was below the limits of detection by TLC, which is a low-resolution technique of analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This comes as a surprise as the literature information from Loranthus micranthus Linn. studies reported the presence of alkaloids in the DCM and MeOH extracts [ 13 ]. Perhaps their presence in the samples we analyzed was below the limits of detection by TLC, which is a low-resolution technique of analysis.…”
Section: Resultsmentioning
confidence: 99%
“…50,64,65 The content, especially the alkaloid group, is known to have the ability as an antioxidant and antibacterial. [66][67][68][69] The solvent used in this research is ethyl acetate which is a semipolar solvent. The ability of ethyl acetate to bind polar and nonpolar compounds so that the secondary metabolites contained in the extract are more varied.…”
Section: Molecular Identification Of Endophytic Fungimentioning
confidence: 99%
“…The results of qualitative tests revealed that the alcoholic extract of A.atemoya seeds contained alkaloids, flavonoids, glycosides, tannins, phenol, and proteins, except for saponins (Table 3). Many studies have confirmed that plants are rich in a variety of secondary metabolites, such as tannins, terpenoids, alkaloids, and flavonoids (Mapfumari et al 2022). Shami (2017) reported that alkaloids isolated from A. squamosa showed good antibacterial and antioxidant activity, so it could be a new source of antimicrobial agents against pathogenic bacteria.…”
Section: Qualitative Analysismentioning
confidence: 99%